Analisis Media Sosial Instagram BPJS Kesehatan dalam Menanggapi Keluhan Masyarakat: English - Dwi Amalia, Rizka; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2024)
This study aims to learn more about how BPJS Kesehatan is implemented in the field in responding to complaints through Instagram social media. The objectives of this study are: 1. to determine the BPJS Kesehatan Service Communication strategy in responding to public complaints through Instagram social media, 2. to determine the supporting and inhibiting factors for providing BPJS Kesehatan communication services in responding to public complaints through Instagram social media. The theories used in this study are New Media Theory and Public Service Theory. New Media Theory and Public Service Theory are still often applied in research, which is the reason why researchers continue to research this theory. This study uses a qualitative research method. The results of this study show how new media is formed through various forms of communication and media that develop with digital technology and the internet. In the context of BPJS Kesehatan, the use of social media platforms such as Instagram to communicate with the public, utilizing interactive features such as comments, DM (Direct Message), and Stories to interact directly and quickly with the public. Instagram makes it easy for BPJS Kesehatan to interact in real-time with users, increasing the level of interconnectedness between service providers and the public. Two-way interaction through comments and direct messages allows direct feedback from the public and a quick response from BPJS Kesehatan. Informative and educational content is delivered through posts, infographics, videos, and Stories, which not only convey information but also build a narrative that brings BPJS Kesehatan closer to users, increasing understanding and awareness of the services provided